2009
DOI: 10.1017/s0043933909000208
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming endangered livelihoods: untold stories of indigenous women and backyard poultry

Abstract: Indigenous women of East Godavari district, Andhra Pradesh, India are unique in that they have over generations protected and bred the world-famous Aseel poultry and other local varieties. Birds managed under backyard systems contribute crucially to women's livelihood, and are of critical cultural importance in the lives of indigenous communities. A combination of factors has resulted in the fast decline of Aseel poultry populations in their traditional locations in the early 1990s. In the past decade, women h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Such a gender bias has been reported in many other developing countries (Gueye, 2007;Keambou et al, 2007;Ramdas, 2009). This bias is the rationale for the use of poultrykeeping programmes as a means of targeting women in poverty alleviation projects, an approach widely known as the "Bangladesh smallholder poultry model" (Jensen and Dolberg, 2003).…”
Section: Socio-economic Aspectsmentioning
confidence: 53%
“…Such a gender bias has been reported in many other developing countries (Gueye, 2007;Keambou et al, 2007;Ramdas, 2009). This bias is the rationale for the use of poultrykeeping programmes as a means of targeting women in poverty alleviation projects, an approach widely known as the "Bangladesh smallholder poultry model" (Jensen and Dolberg, 2003).…”
Section: Socio-economic Aspectsmentioning
confidence: 53%
“…Number (n) and percentages (%) of different feather colours and distribution in local chicken in Kabylie. a gender bias has been reported in many other developing countries (Gueye, 2007;Keambou et al, 2007;Ramdas, 2009). This bias is the rationale for the use of poultrykeeping programmes as a means of targeting women in poverty alleviation projects, an approach widely known as the "Bangladesh smallholder poultry model" (Jensen and Dolberg, 2003).…”
Section: Socio-economic Aspectsmentioning
confidence: 99%
“…Ramdas [ 52 ] reported that native women of East Godavari district, Andhra Pradesh, India, maintained over generations Aseel poultry and other local varieties. Birds managed under backyard system contribute crucially to women livelihood and are of critical cultural importance in the lives of native communities.…”
Section: Importance Of Native Breeds For Rural Economymentioning
confidence: 99%